A Validated Score Predicts Acute Kidney Injury and Survival in Patients With Alcoholic Hepatitis. Issue 12 (4th December 2018) - Sujan, Ravi; Cruz‐Lemini, Monica; Altamirano, Jose; Simonetto, Douglas A.; Maiwall, Rakhi; Axley, Page; Richardson, Taylor; Desai, Vivek; Cabezas, Joaquin; Vargas, Victor; Kamath, Patrick S.; Shah, Vijay H.; et al.
Abstract: Identifying patients at high risk for acute kidney injury (AKI) during hospitalization among patients admitted with severe alcoholic hepatitis (AH) is an unmet clinical need. We performed a multicentric prospective cohort study using data from 4 different cohorts on well‐characterized patients hospitalized with severe AH. Data collected on 773 AH patients from 4 cohorts across the globe were randomly split into test (n = 390) and validation (n = 383) cohorts. We found that 32% of the patients developed inpatient AKI in the test cohort. Approximately 60% of patients met criteria for systemic inflammatory response syndrome (SIRS) at admission. Hepatic encephalopathy, SIRS, and Model for End‐Stage Liver Disease score at admission predicted inpatient AKI with odds ratios of 3.86, 2.24, and 1.14, respectively. The AKI risk score developed using these predictors stratified risk of inpatient AKI to low (score <3), moderate (3‐4), and high (>4). These findings were replicated in the validation cohort. In the whole study cohort, patients with AKI had a lower 90‐day survival (53% versus 77%; P < 0.001). Those with AKI risk score of >4 had significantly lower 90‐day survival as compared with those with risk scores between 3 and 4 and <3 (47% versus 68% versus 88%; P < 0.001). In conclusion, AKI occurs frequently in AH patients and negatively impacts short‐term mortality. The AKI risk score is useful in identifying patients at high risk for inpatient AKI and may be useful for developing new therapeutic strategies to prevent AKI in patients with AH.